Overview on Application of Ozone in the Food Processing Industry - Chennappa Gurikar, Lokesh A C, Hanumantharaju K N, Joshma.T.J, Ganesh.K.N, Modini.B.V (Forest Chemicals Review, 2022)
Antibacterial qualities of ozone have been discovered recently and it is being employed as a potent disinfectant in food industry. Ozone is used in liquid and gaseous forms. Ozone in liquid form can treat water, sterilize equipment, and various types of food. In gaseous form it can be used to sanitize instruments and food packaging materials. The history of ozone, ozone generating processes, ozone physicochemical features, and its application in food processing are  covered in this study. Ozone can be generated by many artificial methods like silent electrical discharge, electrochemical reactions, UV radiation, and Electrolysis. Ozone is recently applied in many fields of the food industry like, food beverages, seafood, fruit and vegetable industry, meat industry and dairy industry and it has shown significant influence in food processing fields.  In addition to this, potential applications concerning the development and application of ozone generation, nutritional and quality aspects of food, and ozone as a disinfectant also have been proposed